Historical biogeography of smoothhound sharks (genus Mustelus) of Southern Africa reveals multiple dispersal events from the Northern Hemisphere. Issue 7 (17th July 2020) - Maduna, Simo N.; Hull, Kelvin L.; Farrell, Edward D.; Boomer, Jessica J.; Veríssimo, Ana; Marino, Ilaria A. M.; Mazzoldi, Carlotta; Zane, Lorenzo; Wintner, Sabine P.; Chesalin, Mikhail V.; da Silva, Charlene; Gubili, Chrysoula; et al.
Abstract : Members of the smoothhound shark genus Mustelus display a widespread distribution pattern across ocean basins with a high degree of sub-regional endemism. The patterns and processes that resulted in smoothhound biodiversity and present-day distribution remain largely unknown. We infer the phylogenetic relationships of the genus Mustelus, based on sequence data (3474 bp) from three mitochondrial genes (CR, NADH-2 and 12S-16SrRNA) and a nuclear gene (KBTBD2) from seven species of Mustelus distributed across the eastern Atlantic- and Indo-Pacific oceans. Using the CR and KBTBD2 dataset, we infer the phylogeographic placement of Old World Mustelus, with particular reference to species from southern Africa. Using a near-complete phylogeny of the genus including Old World and New World species of Mustelus and publicly available sequences of the NADH-2 gene, we found supporting evidence indicating a major cladogenic event separating placental and aplacental species. Biogeographical analyses further revealed that the radiation of Mustelus in the southern African region was driven primarily by long-distance dispersal during the upper Miocene to lower Pleistocene. The placement of the placental blackspotted smoothhound Mustelus punctulatus at the base of the placental non-spotted clade suggests the secondary loss of black spots in the genus, and this was also supported by the ancestral state reconstruction. The results furthermore suggest that the Southern Hemisphere species of the genus arose from multiple separate dispersal events from the Northern Hemisphere which is in line with the earliest record of Mustelus in the Northern Hemisphere.